Extracellular Vesicles Mediate Radiation-Induced Systemic Bystander Signals in the Bone Marrow and Spleen - Szatmári, Tünde; Kis, Dávid; Bogdándi, Enikő Noémi; Benedek, Anett; Bright, Scott; Bowler, Deborah; Persa, Eszter; Kis, Enikő; Balogh, Andrea; Naszályi, Lívia N.; Kadhim, Munira; Sáfrány, Géza; et al. (Frontiers in Immunology, 2017)
Radiation-induced bystander effects refer to the induction of biological changes in cells not directly hit by radiation implying that the number of cells affected by radiation is larger than the actual number of irradiated cells. Recent in vitro studies suggest the role of extracellular vesicles (EV) in mediating radiation-induced bystander signals but in vivo investigations are still lacking. Here we report an in vivo study investigating the role of EVs in mediating radiation effects. C57BL/6 mice were total-body irradiated with X-rays (0.1, 0.25, 2 Gy), 24 hours later EVs were isolated from the bone marrow and were intravenously injected into unirradiated (so-called bystander) animals. EV-induced systemic effects were compared to radiation effects in the directly irradiated animals. Similarly to direct radiation EVs from irradiated mice induced complex DNA damage in EV-recipient animals, manifested in an increased level of chromosomal aberrations and the activation of the DNA damage response. However, while DNA damage after direct irradiation increased with the dose, EV-induced effects peaked at lower doses. A significantly reduced hematopoietic stem cell pool in the BM as well as CD4+ and CD8+ lymphocyte pool in the spleen was detected in mice injected with EVs isolated from animals irradiated with 2 Gy. These EV-induced alterations were comparable to changes present in the directly irradiated mice. The pool of TLR4-expressing dendritic cells was different in the directly irradiated mice, where it increased after 2 Gy and in the EV-recipient animals, where it strongly decreased in a dose-independent manner. A panel of 8 differentially expressed miRNAs were identified in the EVs originating from both low and high dose-irradiated mice, with a predicted involvement in pathways related to DNA damage repair, hematopoietic and immune system regulation, suggesting a direct involvement of these pathways in mediating radiation-induced systemic effects. In conclusion, we proved the role of EVs in transmitting certain radiation effects, identified miRNAs carried by EVs potentially responsible for these effects and showed that the pattern of changes was often different in the directly irradiated and EV-recipient bystander mice, suggesting different mechanisms.